The Impact of Ransomware on Indonesia’s National Data Security: Case Study of Kominfo Data Leaks - Rahmat Rambe; Fairuz Fernanda Hermawan (Indonesian Journal on Computing (Indo-JC), 2025)
Ransomware poses a growing threat to national data security, especially in Indonesia, where government agencies have experienced serious data breaches. This study examines the June 2024 ransomware attack on Indonesia’s Ministry of Communication and Informatics (Kominfo) through a systematic literature review (SLR) of 1,200 articles from Semantic Scholar, Scopus, and IEEE Xplore (2015–2024), narrowing to 45 relevant studies. Findings highlight critical vulnerabilities, including weak technical infrastructure, inadequate backup systems, low password security, poor inter-agency coordination, and a shortage of trained cybersecurity professionals. Governance issues such as ineffective regulation and corruption in procurement further increased systemic risk. Current literature shows limited relevance to Indonesia’s context, as most studies originate from high-income countries. The study recommends strengthening cybersecurity regulations aligned with frameworks like the GDPR, and improving workforce capabilities through targeted training. Cross-sector and international collaboration are also key to building resilience. These strategies are essential to enhance data protection and prevent future breaches.